Bi-phonic voice: a study of the potential for using the extended vibrational qualities of overtone chanting and singing as an intervention in training the speaking voice - Muller, Catherine Margaret (My University, 2015)
This study examines human vocal production through the lens of vibration. The needs of the speaking voice in terms of communication are explored, with particular emphasis on the vocal needs of the professional speaker, where extended range and resonance will ensure optimum communicative effect. As this goal may require training, a comparative study is presented of approaches to vocal training that have the aim of improving resonance and range while minimising damage to the vocal apparatus. These approaches include the quest to overcome physical, societal and emotional blocks to effective vocal production. This comparative study is based on the writings of a selection of popular vocal training theorists’ writings. To enhance the study of effective vocal production, the physical and physiological means of meeting the needs of producing voice are explored, by an interrogation of what vibration is in terms of vocal production. To investigate this, I have examined the physical nature of vibration, followed by the physiological aspect of this vibration as it relates to vocal production. Included in this investigation is an appreciation of what might affect the vibrations of speech that relate to resonance and range, to either enhance or hinder them. Because Bi-phonic voice, or Overtone singing and chanting, uses extended vibrational qualities, this study explores the possibility of using these vibrational qualities in vocal training to extend range and resonance. A brief ethnological study of Bi-phonic voice is presented followed by an examination of its functioning with emphasis on the manner in which the vibrations used may differ from those in western vocal techniques. Experiential reports of Bi-phonic vocal production, obtained through interviews, are presented, which in conjunction with literature on the practice will contribute to ascertaining whether there is in fact potential for using the techniques, without endangering the vocal apparatus, as an adjunct to current vocal training trends.
Research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and research report School of Arts, Drama Division University of the Witwatersrand, Johannesburg, South Africa